Cost-Effectiveness of Antibiotics for Typhoid Fever at Hermana Lembean Hospital - Teodhora, Teodhora; Musnelina, Lili; Tanama, Celin Gracela (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2024)
Salmonella typhi bacteria, which contaminate ingested food and beverages and sufferers' feces, urine, or other secretions, are typically to blame for typhoid fever. This study's objectives were to identify the traits of inpatient typhoid fever patients who received antibiotics evaluating the cost-effectiveness of antibiotics for typhoid fever patients receiving inpatient typhoid fever at Hermana Lembean Public Hospital. The cost-effectiveness of antibiotic therapy for inpatients with typhoid fever was examined in this study utilizing descriptive research, which involved retrospective data collecting using secondary data, such as medical record data and record costs of patients who had received inpatient care at Hermana Lembean General Hospital. According to the calculations from the Cost-Effectiveness Analysis, ceftriaxone injectable therapy has an ACER value of Rp. 15.987, and an efficacy of 100%, is the most economical antibiotic treatment.